2017
DOI: 10.1186/s12866-017-1018-2
|View full text |Cite
|
Sign up to set email alerts
|

FilmArray™ GI panel performance for the diagnosis of acute gastroenteritis or hemorragic diarrhea

Abstract: BackgroundAcute gastroenteritis is a common cause of morbidity and mortality in humans worldwide. The rapid and specific identification of infectious agents is crucial for correct patient management. However, diagnosis of acute gastroenteritis is usually performed with diagnostic panels that include only a few pathogens. In the present bicentric study, the diagnostic value of FilmArray™ GI panels was assessed in unformed stool samples of patients with acute gastroenteritis and in a series of samples collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
2
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 43 publications
(45 reference statements)
6
46
2
6
Order By: Relevance
“…We found that the GI panel had a high (32.8%) positivity rate which was similar to that of other published studies (5)(6)(7)(8). Piralla et al (9) tested 168 adult and pediatric patients with diarrhea and found an overall 54.8% positivity rate, with 28.3% having more than one organism. We found that 24% of positive samples had more than one organism.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the GI panel had a high (32.8%) positivity rate which was similar to that of other published studies (5)(6)(7)(8). Piralla et al (9) tested 168 adult and pediatric patients with diarrhea and found an overall 54.8% positivity rate, with 28.3% having more than one organism. We found that 24% of positive samples had more than one organism.…”
Section: Discussionsupporting
confidence: 90%
“…As these tests become more prevalent in clinical microbiology laboratories, it is essential that adequate evaluation of molecular tests for the diagnosis of gastrointestinal infections is undertaken. Recent evaluation studies demonstrate that the use of molecular-based diagnostics increases the sensitivity of testing for some enteric pathogens, with overall high negative predictive values [4][5][6][7][8][9][10]. However, the UK National Institute for Health and Care Excellence (NICE) published their diagnostics guidance in January 2017 [11], based on a Diagnostic Assessment Report commissioned by the National Institute of Health Research (NIHR) Health Technology Assessment (HTA) Programme [12].…”
Section: Evidence To Support Molecular-based Diagnostic Testingmentioning
confidence: 99%
“…The introduction of molecular technologies into a clinical microbiology laboratory, such as multiplex polymerase chain reaction (PCR) assays, can benefit the diagnosis of gastrointestinal infection by facilitating simultaneous detection of pathogens (bacterial, parasitic and viral) directly from faeces. Molecular-based diagnosis gives a laboratory the potential to increase sample throughput, increase the amount of information obtained from a single test and decrease sample turnaround times [4][5][6][7][8][9][10]. Additionally, simple workflows and a reduction in the need for technical expertise are appealing attributes of these diagnostic methods.…”
Section: Introductionmentioning
confidence: 99%
“…ishalli hastalarda yaptığı bir çalışmada konvansiyonel yöntemlerle %27,7 oranında etken saptarken, multiplex PZR yöntemiyle %66,2 oranında etken saptayabilmişlerdir [4]. Farklı çalışmalarda başka bir multiplex PZR kitiyle etken saptanma oranı %33,0-%62,7 oranında bildirilmiştir [5,6,7,8]. Konvansiyonel yöntemlerle yapılan çalışmalarda gastroenterit etkenleri Hollanda' da %6,4, Amerika Birleşik Devletleri'nde % 8.3, Yeni Zelanda' da %18 olarak saptanmıştır.…”
Section: Discussionunclassified
“…Piralla ve ark. yaptığı çalışmada koenfeksiyon oranı %27,2 olarak bulunmuştur [7]. Bu çalışmadaki koenfeksiyon oranı birçok çalışmaya göre daha azdır (%8,5).…”
Section: Discussionunclassified